Acceleration Time-to-Ejection Time Ratio in Fetal Pulmonary Artery Predicts the Development of Neonatal Respiratory Distress Syndrome: A Prospective Cohort Study - Kim, Sun Min; Park, Joong Shin; Norwitz, Errol R.; Hwang, Eun Ju; Kang, Hye Sim; Park, Chan-Wook; Jun, Jong Kwan (American Journal of Perinatology, 2013)
Objective This study investigates whether fetal pulmonary artery Doppler waveforms can predict the subsequent development of respiratory distress syndrome (RDS).Study Design A prospective cohort study was performed in women with impending preterm birth. Pulsatility index, resistance index, systolic-to-diastolic ratio, peak systolic velocity, and acceleration time-to-ejection time (At/Et) ratio were measured in the main pulmonary artery of fetus just before delivery.Results Neonates who developed RDS (n = 11) had significantly lower gestational age at birth than those without RDS (n = 31; median: 28.7 [range: 24.7 to 34.9] versus 32.9 [range: 25.7 to 36.0] weeks; p = 0.003); there was no difference in antenatal corticosteroid administration. Pulmonary artery At/Et ratio was significantly higher in fetuses that developed RDS compared with those that did not (median: 0.37 [range: 0.26 to 0.41] versus median: 0.30 [range: 0.21 to 0.44]; p = 0.008). RDS prediction score (=a hundredfold At/Et ratio) is significantly associated with the subsequent development of RDS after controlling for gestational age by logistic regression analysis (odds ratio = 1.31, 95% confidence interval 1.05 to 1.63, p = 0.017).Conclusion An elevated At/Et ratio in the fetal pulmonary artery is independently associated with the development of RDS in preterm infants. These data suggest that fetal pulmonary artery Doppler velocimetry may provide a reliable noninvasive technique to evaluate fetal lung maturity, similar to the way in which middle cerebral artery Doppler has replaced amniocentesis for the assessment of fetal anemia.
Keywords: fetal pulmonary artery; Doppler; respiratory distress syndrome; prematurity; preterm birth